1990
DOI: 10.1177/026553229000700204
|View full text |Cite
|
Sign up to set email alerts
|

Self-assessment of second language ability: the role of response effects

Abstract: The role of response effects (tendencies to respond to factors other than item content) in the self-assessment of second language ability was investigated through a split-ballot procedure using positively-and negatively-worded questions and graded (i.e. level-specific questions). Results indicate that both an acquiescence effect (a tendency to respond positively regardless of item content) and overestimation were present. Although both effects were present at all levels of subjects, they were most evident for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
58
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 39 publications
6
58
0
Order By: Relevance
“…It is possible that there may be individual and/or culturally related differences with respect to general response tendencies in ESL (or other second language) self-assessment situations--e.g., to overestimate or underestimate when asked to provide self-ratings of "proficiency" (e.g., Heilenman, 1990;Oskarsson [Oscarson], 1981;Wangsotorn, 1981). The question of tendencies toward over-or underestimation as an individual or "population" characteristic appears to be an important one for further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that there may be individual and/or culturally related differences with respect to general response tendencies in ESL (or other second language) self-assessment situations--e.g., to overestimate or underestimate when asked to provide self-ratings of "proficiency" (e.g., Heilenman, 1990;Oskarsson [Oscarson], 1981;Wangsotorn, 1981). The question of tendencies toward over-or underestimation as an individual or "population" characteristic appears to be an important one for further research.…”
Section: Discussionmentioning
confidence: 99%
“…The more recent (Oscarson, 1989), comprehensive review suggests continued, marked diversity in the purposes, methods, and lines of inquiry subsumed under the" self-assessment" rubric (a theme which is reinforced by Oscarson's [forthcoming] review, based on examination of pre-publication copy, received too late for full consideration in this paper). For perspective regarding conceptual and methodological diversity see, for example, Ingram (1985), Bachman and Palmer (1989), Blanche and Merino (1989), Heilenman (1990), Xu (1991. For present purposes, it seems fair to say that in the field of second language proficiency assessment, interest in developing and evaluating formal self-assessment "instruments" has not been widespread, and very few studies appear to have employed the same or clearly similar instruments/models.…”
Section: Je Connais Presque La Totalite De La Grammaire Anglaise Maimentioning
confidence: 99%
“…Since language proficiency has been found to be a strong source of variation in rating accuracy of self-and peer-assessment (Davidson & Henning, 1985;Blanche, 1988;Janssen-van Dieten, 1989;Heilenmann, 1990), the participants' proficiency level was determined by means of the Oxford Placement Test (OPT). According to Allan (2004), the developer of the test, OPT has been calibrated against the proficiency levels based on the Common European Framework of Reference for Languages (CEF), the Cambridge ESOL Examinations and other major international examinations such as TOEFL.…”
Section: Proficiency Testmentioning
confidence: 99%
“…Ross (1998), looking at second-language assessment, performed a meta-analysis of validation studies and concluded that accuracy in selfassessment depended on the skill being evaluated, and found that writing was among the more difficult skills to self-assess reliably. In addition to variation of the skill under assessment, other researchers have found that other factors can influence the accuracy in self -assessment, such as the learners' proficiency level (Heilenman, 1990, Patri, 2002, second-language anxiety (MacIntyre et al 1997), and motivation (Dornyei, 2001). Butler and Lee (2010) studied the effects of self-assessment on English language learners in South Korea and found that improvements in accuracy were only marginal over time, and that training in the process was critical, as well as providing sustained feedback to the self-assessors.…”
mentioning
confidence: 99%
“…Blanche & Merino, 1989;Harris, 1997;Heilenman, 1990). These questionnaire responses are then compared to teacher evaluations of the students.…”
mentioning
confidence: 99%